HIV Antibody Status and Immunological Abnormalities in Polish Haemophiliacs - Lopaciuk, S; Kacperska, E; Gloskowska-Moraczewska, Z; Maslanka, K; Uhrynowska, M; Kraj, M; Seyfried, H (Thrombosis and Haemostasis, 1987)
Sera of 520 multitransfused haemophiliacs were examined for antibody to HIV; 447 patients had haemophilia A and 73 had haemophilia B. In 382 patients with haemophilia A and in 62 with haemophilia B solely Polish-made blood products were used for replacement therapy. The remaining haemophiliacs had also received imported clotting factor concentrates prior to the investigation. Only 8 patients (haemophilia A - 7, haemophilia B - 1) developed anti-HIV and all of them had been exposed to commercial concentrates. The analysis of T-cell subsets demonstrated an inverted T4/T8 ratio (less than 1.0) in 7 (30%) of the 23 haemophiliacs treated solely with domestic cryoprecipitate and in 3 (37%) of the 8 seropositive recipients of commercial concentrates. The most frequent alteration in both subgroups was a reduced ratio with either normal absolute numbers or an increase in T8 cells. Increased serum IgG levels were found in 82% of the users of cryoprecipitate and in 75% of the seropositive patients. Serum beta-2-microglobulin level was elevated in 69 and 62% of each subgroup, respectively. The observed immunological abnormalities, at least in the cryoprecipitate treated subgroup, may be causally related to factors other than HIV infection.
Keywords: Haemophilia; Replacement therapy; AIDS; HIV antibody; Immunological abnormalities